2019
DOI: 10.1007/s10578-019-00916-2
|View full text |Cite
|
Sign up to set email alerts
|

General Psychopathology and Dysregulation Profile in a Longitudinal Community Sample: Stability, Antecedents and Outcomes

Abstract: The general factor of psychopathology (GP, or p factor) and the Dysregulation Profile (DP) are two conceptually similar, but independently developed approaches to understand psychopathology. GP and DP models and their stability, antecedents and outcomes are studied in a longitudinal sample of 1073 children (49.8% female). GP and DP models were estimated at ages 8 and 14 years using the parent-reported Child Behavior Checklist (CBCL) and Youth Self Report (YSR). Early childhood antecedents and adolescent outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 54 publications
17
61
0
Order By: Relevance
“…[73] significant associations between 10/10 DAT1 genotype and children's psychopathological problems (i.e., ADHD) have been found. Subsequently, many studies have replicated the same association for children's other psychopathological difficulties [60][61][62][63][64][65][66][67][68], as also our study confirmed. However, to our knowledge, this is the first study to show that children's DAT1 polymorphism can significantly correlate with emotional-behavioral dysregulation among early childhood.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[73] significant associations between 10/10 DAT1 genotype and children's psychopathological problems (i.e., ADHD) have been found. Subsequently, many studies have replicated the same association for children's other psychopathological difficulties [60][61][62][63][64][65][66][67][68], as also our study confirmed. However, to our knowledge, this is the first study to show that children's DAT1 polymorphism can significantly correlate with emotional-behavioral dysregulation among early childhood.…”
Section: Discussionsupporting
confidence: 87%
“…This imbalance plays a crucial role in an individual's disease susceptibility, and studies on clinical samples have shown that DAT1 was associated with different psychopathological difficulties, from infancy to adulthood, including attention-deficit hyperactivity disorder (ADHD) [50][51][52][53], conduct disorder [54], affective disorders [55,56], post-traumatic stress disorder [57], and eating disorders [58,59]. A couple of studies have focused on the general population, showing significant associations with children's temperament traits (including uninhibited traits, negative emotionality, aggressive and impulsive traits) [60][61][62], symptoms of ADHD [63,64], and other subclinical forms of psychological difficulties in both internalizing and externalizing areas [65][66][67][68]. However, to date, only a few studies have focused on early childhood [61,62], and to our best knowledge, no studies have explored the possible association between children's DAT1 polymorphism with children's dysregulation profile (DP), an empirically-based profile of poor self-regulation among early childhood [69], with which prospective associations with psychopathological difficulties have been evidenced over time [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three key concepts in the developmental psychopathological literature: (a) the childhood dysregulation phenotype or profile; (b) co‐developing internalising and externalising symptom profile; and (c) the general psychopathology or ‘p’ factor. The p factor is the broadest of these three concepts and comprises internalising, externalising and thought disorder components (Deutz et al., ). Here, we focus on the first two concepts as most relevant to our study (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of children and adolescents who are referred to clinical treatment present with self-regulation difficulties in emotional, behavioral and cognitive domains (Deutz et al 2018;Holtmann et al 2007). These are not unique to a specific diagnostic category (Ayer et al 2009;Carballo et al 2014;Legenbauer et al 2018), but are rather described within the transdiagnostic so-called dysregulation profile (DP; Deutz et al 2018Deutz et al , 2020Althoff et al 2010;Ayer et al 2009). The DP reflects a profile of elevated scores on subscales of the widely used Child Behavior Checklist (CBCL; Achenbach 1991) or the Strengths and Difficulties Questionnaire (SDQ; Goodman et al 1998;Holtmann et al 2011;Deutz et al 2018;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%